PARADIGMA BARU KONSEP PENDIDIKAN ISLAM PERSPEKTIF SYEIKHUL ISLAM IBN TAIMIYAH - Achmad Fageh (Universitas Islam Lamongan, 2017)
Islamic education is one field of Islamic studies who received a lot of attention from scientists. This is because in addition to a very strategic role in order to enhance human resources, as well as in Islamic education there are a variety of complex problems. Ibn Taymiyyah for example, he was known as a scholar, thinker and politician. The thinking in the field of education is a response to the various problems facing the Islamic society that demands split logically through education. Philosophy of education, he said, should be built on the foundation of monotheism, the belief in the oneness of God. Monotheism which is the basis of education include; rububiyah monotheism, monotheism asthma wa uluhiyah and nature. Based on the insights of faith is then Ibn Taymiyyah describes the purpose of education, students, teachers, curriculum and so on.Keyword: Educational Thought, Relevance, Contemporary